Klinik Hukum Peningkatan Partisipasi Masyarakat Dalam Penyusunan Rencana Zonasi Wilayah Pesisir dan Pulau-Pulau Kecil - Haris Retno Susmiyati; Rahmawati Al Hidayah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Public participation in the preparation of regional regulations is a right guaranteed by the constitution, especially if the regulations to be made are closely related to the sustainability of the community's living space. This is what underlies community service activities carried out to the coastal communities of Balikpapan Bay through groups of fishermen and activists who focus on environmental and coastal issues with the aim of providing legal understanding and awareness to be involved or participate in the preparation of RZWP3K. With the FGD method through 3 stages which include presentation of material, identification of problems, and preparation of policy briefs, it is hoped that it will be able to provide concrete efforts for community participation in the preparation of regional regulations. Based on the results of community service activities, legal awareness was formed for the participants who attended, as evidenced by the involvement of all participants in the preparation of a policy brief that was submitted to the Kaltim DPRD - Special Committee on the Draft Regional Regulation. at RZWP3K East Kalimantan